Isolation and preliminary identification of active compounds from the stem of leea indica (memali) using chromatographic technique / Naila Nabihah Mohd Azam - Mohd Azam, Naila Nabihah (Faculty Of Applied Sciences, 2016)
Leea indica is a medicinal plant that has been widely used as traditional remedy in curing many diseases. This study focused on isolation and preliminary identification of active compounds from the three different stem extracts of L. indica that have anti-oxidant and anti-microbial properties. The isolated active compounds from dichloromethane (DCM) extract at Rf 0.17 and Rf 0.25 was identified as 9-0ctadecane and Aromatic compound after subjected to FTIR, NMR and GC-MS. In DPPH radical scavenging activity analysis, all of the three extracts exhibit anti-oxidant properties where only methanol (MeOH) extract is the most anti-oxidative. The IC50 of MeOH extract is 1.14 ug/ml, which exceed the IC50 of Ascorbic acid (standard) which only 1.12 ug/ml. The stem extracts of this plant exhibit both anti-oxidant and anti-microbial properties. MeOH stem extract showed the strongest anti-oxidant activity due to presence of phenolic compound in the extract which known as strong radical scavengers. The stem of L. indica was proved containing active compounds that have anti-oxidant and anti-microbial properties.